New Locked-Wire-Type External Fixator (the Ichi-Fixator) for Fourth and Fifth Carpometacarpal Joint Dislocation - Ichihara, Satoshi (Case Rep Orthop, 2018)
We developed a new fixation method that involves the insertion of two wires and external wire fixation using a metal clamp. The aim of this technique was to increase the stability and rigidity of conventional percutaneous Kirchner wire fixation. Here, we present a patient with dislocation of the fourth and fifth carpometacarpal joints who was satisfactorily treated with closed reduction and percutaneous fixation with a linking external wire fixator (Ichi-Fixator). Operative treatment using the Ichi-Fixator system facilitates anatomical reduction and immediate full mobilization, resulting in good outcomes. The patient could perform all routine activities with normal grip strength and a full range of hand motion without pain. Such a treatment that improves comfort after the operation and may allow an immediate return to work will clearly boost patient satisfaction. Linked external wire-type fixation enables enhanced security of fixation, facilitates postoperative mobilization, and may allow an immediate return to work.